Bioremediation Performance of Sphingomonas melonis and Bacillus muralis on Herbicide Diquot Dipremide-(ethylene-d4) - Durmus, Mehmet Harun Bogacbarbaros; Aydın, Ekrem; Erguven, Gokhan Onder; Yildirim, Numan; Koçak, Emel (My University, 2022)
Bioremediation is a process that utilizes the degradation potential of microorganism to provide a cost-effective and reliable\rapproach for pesticide biodegradation. For this purpose, chosen bacteria Sphingomonas melonis and Bacillus muralis were isolated\rfrom an agricultural soil sample. The biodegradation performance of these isolated bacteria at different Diquot Dipremide-\r(ethylene-d4) (DDE4) herbicide concentrations (250, 500 and 1000 ppm) was investigated under submerged culture conditions.\rBiodegradation performance of isolated bacteria was monitored with COD, TOC and, BOD5 reduction rates in culture medium at\rdifferent incubation periods. According to the results; S. melonis has the highest bioremediation capacity for COD removal (91%\rat 250 ppm). For TOC, B. muralis has the highest removal rate as 82% at 250 ppm. On the other hand, For BOD5 at 250 ppm 85%\rS. melonis showed the best removal performance. Most effective removal rate at 250 ppm concentrations was obtained as 91%\rand 88 by S. melonis and B. muralis respectively at the end of the 216th hour for COD. Additionally, the increase in turbidity\rrelated with population dynamics at the end of the 216 th hour positively effected the bioremediation parameters included COD,\rTOC and BOD5 reductions. These results showed that it can be used for effective COD, TOC and BOD5 removal in S. melonis and\rB. muralis on DDE4 remediation
Keywords: Biyoloji; Yeşil; Sürdürülebilir Bilim ve Teknoloji; Çevre Bilimleri; Veterinerlik